Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Leverage Terhadap Enviromental Disclosure - Atika Meliana Putri; Dirvi Surya Abbas; Dewi Rachmania (Jurnal Akuntan Publik, 2023)
This purpose  of this research is to examine the effect of firm size, profitability, leverage on environmental disclosure with competitive advantage as moderation. The research period is 3 years starting from 2019 to 2021. There are 64 manufacturing companies listed on the Indonesian stock exchange. sample selection using purposive sampling method. Hypothesis testing is done by using panel data regression analysis. The results of the study indicate that company size has a positive effect on environmental disclosure. Profitability, have no effect on environmental disclosure.